2012
DOI: 10.1177/0010414012453032
|View full text |Cite
|
Sign up to set email alerts
|

The Source of Turnout Decline

Abstract: Voter turnout has consistently declined since the 1980s across a wide range of advanced democracies. Much of this decline appears to be the result of young people abstaining. In this article the authors test two arguments for this trend. The first rests on the claim that the character of elections has changed, specifically that elections have become less competitive and that young people’s propensities for voting are particularly negatively affected by this. The second maintains that recent generations have di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(46 citation statements)
references
References 21 publications
1
41
0
4
Order By: Relevance
“…Further research is required to determine how the political participator types identified in the current study may vary over time. While the limited availability of long-term longitudinal data on attitudes and political participation is well known (Blais and Rubenson 2013), particularly outside of electoral participation, future research on this topic will benefit from the recent development of several high-quality longitudinal data sets in a number of countries such as Belgium (Hooghe et al 2015) and Sweden (Amnå et al 2009). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further research is required to determine how the political participator types identified in the current study may vary over time. While the limited availability of long-term longitudinal data on attitudes and political participation is well known (Blais and Rubenson 2013), particularly outside of electoral participation, future research on this topic will benefit from the recent development of several high-quality longitudinal data sets in a number of countries such as Belgium (Hooghe et al 2015) and Sweden (Amnå et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Increases in the prevalence of these citizenship norms—variously referred to as “engaged” (Coffé and van der Lippe 2010; Dalton 2008, 2015), “critical” (Geissel 2008; Norris 1999, 2011), “self-actualizing” (Bennett 2008, 2012; Shehata et al 2015; Wells 2014), and “emancipative” (Welzel 2007, 2013)—are identified as motivating increasingly common acts of non-institutionalized participation. Cross-national empirical investigations of these claims indeed suggest that a decline in duty-based norms has led to decreased institutional participation such as voter turnout (Blais and Rubenson 2013), while certain types of “good citizenship” norms are associated with some non-institutionalized activities such as protest (Welzel and Deutsch 2012), albeit with weaker effects in new and less developed democracies (Bolzendahl and Coffé 2013). …”
Section: Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Two weeks before the election, nearly 200,000 had not enrolled (Whelan and Hunt 2014). Young people are invariably less likely to vote than older people, but if the age gap grows (because voting is habitual and best acquired young, as they age young non-voters become older non-voters), we will see the generational replacements of keen voters with apparently more indifferent non-voters (Blais and Rubenson 2013;Franklin 2004;Vowles 2010; see also Rusk et al 2004;Dalton 2007;Lyons and Alexander 2000;Wass 2007;Wattenberg 2007). …”
Section: Electoral Turnout and Inequalitymentioning
confidence: 99%
“…Attempts at broadening this conceptualization often coil back to electoral activities such as volunteering time or money to campaigns (Valentino et al, 2011). At the same time, voting rates are low in contemporary democracies (Blais & Rubenson, 2013;Norris, 2002) and election-centric activities are not an integral part of daily life. These definitions also leave little room for understanding dimensions of participation that no longer occur in the physical world.…”
Section: Elections As the Canon Of Participationmentioning
confidence: 99%